Clinical and surgical management of ankle fractures Weber B. Traumatology and Orthopedics Department. Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2024)
Ankle fractures are one of the most common bone injuries in the trauma emergency department, representing a high percentage of lower limb fractures. The aim of this research work was to determine the clinical-surgical management of patients with Weber B ankle fractures who attended the Traumatology and Orthopedics Service at the Dr. Antonio María Pineda Central University Hospital during the period January 2022 to January 2023. Two hundred patients with a mean age of 39.56 ± 13.42 years were included. Pain and functional limitation was present in all cases. Other symptoms included edema (97%), crampy bony ankle deformity (43%) and bony exposure (6%). The left side was the most affected (53%). Eighty percent of the patients received surgical treatment. The patient's evolution was favorable in 70% of the cases; 72% received post-surgical rehabilitation. However, treatment failure was observed in 10% of the patients, many of them belonging to the conservative management group.